Lesões por causas externas e fisioterapia: estudo em um centro de reabilitação municipal de média complexidade de Uberlândia MG - Lemos, Carla Andréa Gondim (2010)
The morbidity and mortality from external causes is a significant point in the epidemiological transition in the country, due to the large number of victims, particularly young workers who develop disabilities requiring care and treatment services, which creates a personal reflection, family and social negative. Since most studies focus on the question of mortality, little is known about the evolution of non-fatal victims. Due to the scarcity of research regarding this aspect, we carried out this descriptive study. Data were collected prospectively from 285 patients victims of external causes who received primary care at the Rehabilitation Centre Municipal de Uberlândia (CEREM), MG in the period from January to July 2005. This study aimed to characterize the external causes that motivated the search for CEREM, the physiotherapy treatment and the evolution of the patients. It was used as a tool for obtaining the data used a semistructured questionnaire on two occasions: on admission to the service and upon his discharge. Addressed to aspects related to the patient, the lesion causing the event, to care, to physiotherapy treatment, the functional outcome. In cases where treatment was discontinued, close to the protocol, we attempted to telephone contact with the patient, personal contact with the professional responsible for care, and information in the records of medical records. It was found that almost all patients (280, 98.2%) were from Uberlândia, mostly male (161, 56.5%) aged between 20 and 59 years (217, 76, 2%), and unstable marital relationship (144, 50.5%). Regarding the to schooling, most people (194, 68.1%) had not completed high school, exercised occupations that required little qualification (38 general services, 13.3%, construction workers, 31, 10, 9%), presenting, therefore, of less than three minimum wages (133, 46.6%). During treatment, 185 patients (65%) had a formal job and of these, 129 (69.7%) were away from work for an average of 66 days, most had no health plan (220, 77.2 %). The accidents were responsible for most injuries (274, 96.1%) among them, falls (124, 43.5%) and traffic accidents (83, 29.1%) stood out, resulting mainly fractures (191, 62.2%) with predominant involvement of upper limbs (156, 51.6%). Nearly half the events occurred on public roads (135, 47.3%). The public network originated 98.6% of referrals (281). The median time from injury to the request for physiotherapy was 56 days, and waiting for the start of treatment after 48 days of your request. Of the 285 patients admitted students, 198 (69.5%) completed the treatment, performing an average of 17 sessions; kinesiotherapy (228, 82.3%), electrotherapy (211, 76.1%) and thermotherapy for the addition ( 200, 72.2%) were the most used therapeutic resources. In 27.7% of cases (79), treatment was interrupted for several reasons. Initially, when joining the service, the majority of respondents complained of pain (240, 84.2%) and decreased range of motion of the joint or segment involved in the lesion (244, 85.6%). However, despite this fact, most (177, 62.1%) reported independence in relation to performing their daily activities. Of those who completed treatment (198, 69.5%), the majority reported complete relief of pain (116, 58.5%), total recovery of movements (122, 61.6%) and independence in carrying out its activities daily life (191, 96.4%) after intervention. It follows that people affected by external causes that need to be rehabilitated in specialized centers are predominantly male, aged between 20 and 59 years, which have low education and income, have occupations requiring little qualification, besides not have a health insurance plan. Formal employment relationship is common among respondents and almost half of them away from work temporarily in light of the injuries, which are mainly caused by accidents occurring on public roads, resulting mostly in fractures with involvement of upper limbs. Referrals for physiotherapy comes almost exclusively from public service, and the elapsed time of occurrence of the injury to the request for physiotherapy an average of 56 days, and this the beginning of treatment 48 days. Almost 70% of treatments started are completed with an average of 17 sessions, with exercise, electrotherapy and thermotherapy by adding the resources most commonly used treatment. Overall, patients treated by physiotherapy independent completing treatment or do not show good response with respect to the control of pain, the gain range of motion and level of independence in their daily activities.